Acquisition of double mutation in gyrA caused high resistance to sitafloxacin in Helicobacter pylori after unsuccessful eradication with sitafloxacin‐containing regimens. Issue 3 (1st April 2018) - Mori, Hideki; Suzuki, Hidekazu; Matsuzaki, Juntaro; Masaoka, Tatsuhiro; Kanai, Takanori
Abstract : Background and aim: Although sitafloxacin (STFX)‐containing regimens are effective rescue treatments for Helicobacter pylori infection, prevalence of fluoroquinolone resistance in H. pylori has increased rapidly worldwide. The change in resistance levels and gyrA mutations, a major cause of fluoroquinolone resistance, after unsuccessful STFX‐containing treatment has not been investigated. Methods: We conducted a retrospective, non‐randomized study to compare the minimum inhibitory concentrations (MICs) of STFX and the location of gyrA mutations in H. pylori before and after unsuccessful eradication with STFX‐containing regimens at Keio University Hospital between December 2011 and March 2015. Results: A total of 266 patients treated with STFX‐containing regimens for third‐line H. pylori eradication were evaluated. Double mutations in gyrA were acquired by 20.8% of strains that exhibited seven‐fold increased STFX MICs, compared to pre‐treatment MICs. The STFX MICs did not increase, however, when the location of the gyrA mutations did not change after treatment. Double mutations in gyrA developed in 60.0% of the strains in which eradication failed, which exhibited a baseline mutation at position D91, and in 11.1% of strains with baseline mutations at position N87. Conclusion: Acquisition of double mutations in gyrA evoked high‐level resistance to STFX in H. pylori after unsuccessful eradication with STFX‐containing regimens.